Behavioral and Psychological Factors Associated with 12-Month Weight Change in a Physical Activity Trial - Melissa A. Napolitano; Sharon Hayes (Journal of Obesity)
Examining behavioral and psychological factors relating to weight stability over a 1-year period is of public health importance. We conducted a physical activity (PA) intervention trial for women (N=247; mean age=47.5±10.7; mean BMI=28.6±5.3) in which participants were assigned to one of three groups (two PA and one contact-control). By Month 12, participants achieved 140.4±14.82 min of PA/week, with no group differences. Weight status change from baseline to Month 12 was categorized: no change (N=154; 62.4%); increase (N=34; 13.8%); decrease (N=59; 23.9%). Discriminant function analyses indentified two statistically significant dimensions associated with weight change. Dimension 1 was positively weighted by mood (0.73) and self-efficacy (0.79); dimension 2 was positively weighted to change in physical activity (0.58) and fat consumption (0.55). Results provide further evidence for the importance of behavior in long-term weight maintenance, particularly physical activity and dietary fat. These findings also provide evidence for the importance of addressing psychosocial variables, in particular depressed mood and self-efficacy.